Distributed Big Data Frameworks and High-Scale Service Design: Proven Engineering Patterns Across Cloud-Native Deployments - Devinder Tokas (International Journal of Computational and Experimental Science and Engineering, 2026)
Cloud platform engineering is a merger of distributed systems design, data-intensive computing, and reliability engineering to provide resilient services on a global scale. This article explores historical architectural patterns, including batch analytics, streaming backbones, globally replicated databases, and container orchestration, as viewed through well-documented deployment experiences and broadly reusable platform practices. The co-designing of the data plane and the control plane is related to reliability governance in terms of service-level objectives (SLOs) and error budgets, which are extrapolated to fintech, e-commerce, media, and IoT. Throughout these verticals, structural principles are recurrent: consistency trade-offs are intentional, long-lasting log abstractions, orchestrating via reconciliation, and replicating based on the workload. The article ends with a vendor-neutral composable blueprint that unifies these principles into a layered reference architecture that can be applied in deployments over cloud-native platforms.